Efeitos da orientação para a aprendizagem e da segurança psicológica nos conflitos nas equipas - Passos, Ana Margarida (2011)
This study aimed to evaluate the impact of two specific dimensions of team climate (learning orientation and psychological safety), as a cognitive contextual factor, on different types of team conflict. We hypothesized that the relationship between learning orientation and the different types of conflict is moderated by psychological safety climate. A total of 218 teams (959 individuals) participated in this study. All teams were enrolled in a strategic and management competition for a 5-week period. Globally, the results supported the hypotheses concerning the direct influence of team climate on intragroup conflicts, since more positive climates diminish team conflict. The results also supported the hypothesis of the moderating role of psychological safety on the relationship between learning orientation and both relationship conflict and temporal conflict. Learning orientation diminishes both relationship and temporal conflicts when teams experience high levels of psychological safety. These results point out the importance of team climates on processes and dynamics among members.